Performance evaluation of fuzzy-based decision system for pool - Chua, S.C.; Wong, E.K.; Koo, V.C. (ELSEVIER SCIENCE BV, 2007)
An important step in any machine intelligence is to automatically and reliably decide on a solution/outcome based on the inputs given. The mapping of the inputs to an output decision often follows a set of critical rules that mimic the decision that would often be decided by a human being. In this paper, the performance of a fuzzy-based decision system for playing a game of pool is presented by comparing the results involving direct hit with two known systems. The performance is also compared to the decision that would be made by the human players. The design steps for the fuzzy-based decision system are presented using the fuzzy logic approach by employing a three-input one-output fuzzy inference system based on a set of 24 rules. The results have shown that fuzzy logic is able to accurately decide on the best move, which is as good as the human players themselves. (C) 2005 Elsevier B.V. All rights reserved.